ECG interpretation and commentary - Rafla, Samir; Mokhtar, Ahmed; Kamal, Amr (Journal of Cardiology and Cardiovascular Medicine, 2020)
This is demonstration of selected ECGs for learning or for exams; guided by lessons from great teachers as Prof. Hein Wellens MD. Here we provide advanced examples with comment and analysis.